2009
DOI: 10.2353/ajpath.2009.090212
|View full text |Cite
|
Sign up to set email alerts
|

α7 Nicotinic Acetylcholine Receptor Regulates Airway Epithelium Differentiation by Controlling Basal Cell Proliferation

Abstract: Airway epithelial basal cells are known to be critical for regenerating injured epithelium and maintaining tissue homeostasis. Recent evidence suggests that the ␣7 nicotinic acetylcholine receptor (nAChR), which is highly permeable to Ca 2؉ , is involved in lung morphogenesis. Here, we have investigated the potential role of the ␣7 nAChR in the regulation of airway epithelial basal cell proliferation and the differentiation of the human airway epithelium. In vivo during fetal development and in vitro during th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
76
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(85 citation statements)
references
References 65 publications
6
76
0
Order By: Relevance
“…However, the airways of uninjured ␣7 nAChR-deficient mice also had significant areas with disrupted morphology and basal cell hyperplasia. 4 Nevertheless, the data presented are consistent with the work of others showing that ␣7 nAChR-deficient mice are sensitive to acute lung injury and have deficiencies in fluid clearance mediated by alveolar epithelium. 6 In this study, acute nicotine treatment facilitated recovery from acute lung injury; however, whether chronic low-dose nicotine administration would have a deleterious effect was not tested.…”
supporting
confidence: 82%
See 3 more Smart Citations
“…However, the airways of uninjured ␣7 nAChR-deficient mice also had significant areas with disrupted morphology and basal cell hyperplasia. 4 Nevertheless, the data presented are consistent with the work of others showing that ␣7 nAChR-deficient mice are sensitive to acute lung injury and have deficiencies in fluid clearance mediated by alveolar epithelium. 6 In this study, acute nicotine treatment facilitated recovery from acute lung injury; however, whether chronic low-dose nicotine administration would have a deleterious effect was not tested.…”
supporting
confidence: 82%
“…Specifically, the authors found that the injury response in airways of ␣7 nAChR-deficient mice was characterized by significant basal cell hyperplasia compared with wild-type mice. 4 Treatment of cultured human airway cells or ex vivo human lung explants with ␣-bungarotoxin, a neurotoxin capable of blocking ␣7 nAChR function, had a similar effect on the injury response. As a direct demonstration that ␣7 nAChR expression controls proliferation in cultured cells, a human lung basal epithelial cell line transfected with either small interfering RNA or cDNA (to deplete or enhance ␣7 nAChR expression) showed an inverse correlation between the level of ␣7 nAChR expression and the Supported by the Emory Alcohol and Lung Biology Center (National Institutes of Health [NIH] grant P50-AA013757 to J.R. and M.K.…”
mentioning
confidence: 95%
See 2 more Smart Citations
“…Moreover, a number of nonneuronal cells, including T cells, macrophages, and airway epithelial cells, express nAChRs and may synthesize acetylcholine 27. Although not yet examined for gallbladder epithelium, in the airway nAChRs are expressed by epithelial cells28, 29 and nicotine has been demonstrated to decrease mucus transport,30 increase mucin expression and mucus secretion,31, 32 alter mucus hydration, and increase the viscosity of mucus 33. Nicotine also has been described to cause relaxation of guinea pig gallbladder by a mechanism independent of nAChRs 34.…”
Section: Discussionmentioning
confidence: 99%